AB0627 Predictors of Ild and Its Progression in A Cohort of Scleroderma Patients from Western India: A Prospective Observational Cohort Study. (15th July 2016) - Gc, Y.; Samant, R.; Mahashur, A.; Sagdeo, P.S.; Kakade, G.
Abstract : Background: Pulmonary involvement, including both interstitial lung disease (ILD) and pulmonary arterial hypertension (PAH), has become the primary cause of Scleroderma-related death. Little data has been published from India regarding the progression of ILD and Pulmonary arterial hypertension in Scleroderma. Objectives: 1) To identify baseline factors predictive of ILD and its outcome in patients with Scleroderma. 2) To study the progression of ILD and PAH in scleroderma patients 3) To study the demographic and clinical profile of scleroderma patients from Western India. Methods: Prospective observational study involving 68 patients. Patients were evaluated at 0, 3, 6, 9 and 12 months. Patient's demographic and clinical details were recorded at baseline. Other than routine tests, Anti-nuclear antibodies (ANA), Spirometry, diffusing capacity of lung for carbon monoxide (DLCO) measurement, high resolution computed tomography (HRCT) of thorax, 6-minute walk test and echocardiography were done. Results: Study included 68 individuals with Scleroderma (according to the American College of Rheumatology classification criteria for SSc) with majority of cases being females n=64 (94.1%). ILD was seen in 53 (77.9%) patients with a mean duration of 4.17 years. When we compared the mean change in FVC, DLCO and PAH from the time of onset of ILD/PAH to the values at last follow up, there was no significant change. ILD patients with UIP pattern on HRCT, showed a significant progression in terms of >10% fall in FVC as compared to NSIP subgroup. None of the baseline parameters were predictive of ILD and its progression. Older age predicted onset of PAH. Conclusions: 1) None of the studied baseline variables were predictive of ILD and its progression. 2) Only age had statistically significant effect as a predictor for the occurrence of PAH. 3) The demographic and clinical profile of our cohort was comparable to other studies from India and western population. Calcinosis and telangiectasia were less frequently seen as compared with western population. References: Kumar U, Ramteke R, Yadav R, Ramam M, Handa R, Kumar A. Prevalence and predictors of pulmonary artery hypertension in systemic sclerosis. J Assoc Physicians India. 2008 Jun;56:413–7. Disclosure of Interest: None declared